(untitled) (Research, Society and Development, 2023)
Knowing that training in a theoretical-practical approach to work in clinical psychology has numerous impacts on the professional career, the objective of this study was to understand the reports of beginning clinical psychologists about training in clinical psychology in professional practice . This is a field research, of an exploratory and descriptive nature, with a quantitative and qualitative approach. The participants were 20 clinical psychologists who had just started working and graduated from psychology courses at public universities and private colleges in the state of Paraíba/PB, the majority (75%) being female and with a time of experience in clinical psychology between 1 month and a half to 3 years. The socio-demographic/professional questionnaire and a semi-structured interview were used as instruments. The data from the interviews were analyzed using the IRAMUTEQ program through the Word Cloud technique. To deepen the data, the Thematic Categorical Analysis was used and the questionnaire data were explored through descriptive statistics. The results indicate the importance of good academic training for choosing and acting in clinical psychology and that entering the job market can pose risks to the mental health of beginning clinical psychologists. In this sense, it is concluded that it is important to know the experience of the first years of clinical practice and to build possible mental health care tools for this public.